Nature and Scope of Violence Against Women in San Diego (California), 1996-1998 - Pennell, Susan ([Verlag nicht ermittelbar], 2001)
The goal of this study was to compile and analyze data about incidents of domestic violence in San Diego County, California, in order to enhance understanding of the nature and scope of violence against women. The following objectives were set to achieve this goal: (1) to develop a standardized interview instrument to be used by all emergency shelters for battered women in the region, and (2) to conduct interviews with shelter staff. For this study, the San Diego Association of Governments (SANDAG) collected information about domestic violence in San Diego County from clients admitted to battered women's shelters. The Compilation of Research and Evaluation (CORE) intake interview (Part 1) was initiated in March of 1997. Through this interview, researchers gathered data over a 22-month period, through December 1998, for 599 clients. The CORE discharge interview (Part 2) was theoretically completed at the time of exit with each client who completed the CORE intake interview in order to document the services received. However, data collection at exit was not reliable, due to factors beyond the researchers' control, and thus researchers did not receive a discharge form for each individual who had an intake form. For Part 1 (Intake Data), demographic variables include the client's primary language, and the client and batterer's age, education, race, how they supported themselves, their annual incomes, and their children's sex, age, and ethnicity. Other variables cover whether the client had been to this shelter within the last 12 months, the kind of housing the client had before she came to the shelter, person's admitted along with the client, drug and alcohol use by the client, the batterer, and the children, relationship between the client and the batterer (e.g., spouse, former spouse), if the client and batterer had been in the military, if the client or children were military dependents, the client's citizenship, if the client and batterer had any physical/mental limitations, abuse characteristics (e.g., physical, verbal, sexual, weapon involved), and the client's medical treatment history (e.g., went to hospital, had been abused while pregnant, witnessed abuse while growing up, had been involved in other abusive relationships, had attempted suicide). Additional variables provide legal information (number of times police had been called to the client's household as a result of domestic violence, if anyone in the household had been arrested as a result of those calls, if any charges were filed, if the client or batterer had been convicted of abuse), if the client had a restraining order against the batterer, how the client found out about the shelter, the number of times the client had been admitted to a domestic violence shelter, the client's assessment of her needs at the time of admittance, and the interviewer/counselor's assessment of the client's needs at the time of admittance. Part 2 (Discharge Data) provides information on services the client received from the shelter during her stay (food, clothing, permanent housing, transitional housing, financial assistance, employment, education, medical help, assistance with retrieving belongings, assistance with retrieving/replacing legal documents, law enforcement, temporary restraining order), and services this client received as a referral to another agency (attorney, divorce, child care, counseling, transportation, safety plan, victim/witness funds, mental health services, department of social services, Children's Services Bureau, help with immigration, drug treatment).